1993
DOI: 10.1063/1.858854
|View full text |Cite
|
Sign up to set email alerts
|

On the two-way interaction between homogeneous turbulence and dispersed solid particles. I: Turbulence modification

Abstract: The modification of decaying homogeneous turbulence due to its interaction with dispersed small solid particles (d/v < l), at a volumetric loading ratio $,<5 X lo-", is studied using direct numerical simulation. The results show that the particles increase the fluid turbulence energy at high wave numbers. This increase of energy is accompanied by an increase of the viscous dissipation rate, and, hence, an increase in the rate of energy transfer T(k) from the large-scale motion. Thus, depending on the condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
331
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 533 publications
(364 citation statements)
references
References 21 publications
28
331
5
Order By: Relevance
“…Kenning & Crowe 1997); however, these kinetic energy increases were generally attributed to either droplet wake or gravitational effects and occurred only for large droplets having D/l > 10 −1 where l is the integral lengthscale of the turbulence (e.g. Elghobashi & Truesdell 1993). Thirdly, the streamwise component energy is slightly increased by the droplets at the centreline (figure 19a); this is due to the influence of negative slip velocities in regions of decelerating gas flow within the high-concentration braids structures (figure 10a) which serve as a source of gas phase kinetic energy.…”
Section: Second-order Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kenning & Crowe 1997); however, these kinetic energy increases were generally attributed to either droplet wake or gravitational effects and occurred only for large droplets having D/l > 10 −1 where l is the integral lengthscale of the turbulence (e.g. Elghobashi & Truesdell 1993). Thirdly, the streamwise component energy is slightly increased by the droplets at the centreline (figure 19a); this is due to the influence of negative slip velocities in regions of decelerating gas flow within the high-concentration braids structures (figure 10a) which serve as a source of gas phase kinetic energy.…”
Section: Second-order Statisticsmentioning
confidence: 99%
“…Elghobashi & Truesdell 1993). Gore & Crowe (1989) compiled results from a variety of experiments which suggest that solid particles can act either to dissipate or to enhance turbulence energy depending on the diameter of the particles relative to the integral lengthscale of the flow; however, no conclusions could be drawn as to the magnitude of the modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the very high numerical demands, most of these have used a number of simplifications: the dispersed phase is often modelled as point particles (Elghobashi & Truesdell 1993;Boivin, Simonin & Squires 2000). Rather than solving the full equation of motion of the particles, it is usually considerably simplified by considering cases with a large density ratio (Squires & Eaton 1990;Ferrante & Elghobashi 2003).…”
Section: Earlier Workmentioning
confidence: 99%
“…Gore & Crowe (1989) suggested that turbulence will be augmented or suppressed depending on the ratio of particle dimension to a turbulent length scale. Elghobashi & Truesdell (1993) concluded that 'the particles, due to their inertia impart their energy to the turbulent motion at high wavenumbers with a corresponding increase in the dissipation. The enhanced dissipation signals the smaller wavenumbers (larger scales), to supply more energy to the highly active small scales, at a rate higher than that of the particle-free case'.…”
Section: Introductionmentioning
confidence: 99%